PENDIDIKAN BERKELANJUTAN DAN PERAN UNIVERSITAS TERBUKA - Nuraini Soleiman (LPPM Universitas Terbuka, 2010)
Continuing education is a term that usually used to provide education for adult students, in upgrading their knowledge in a particular field of study and therefore it can be in the form of a certificate or degree programs. The certificate programs which is combined with a transfer credit system is becoming more relevance for adult students who work. After 24 years of participating in providing education for adult learner, UT has many experiences in providing programs through distance education mode, including the experience of the credit transfer system.UT has 4 faculties that provide programs in degree programs and therefore UT already developed printed course materials about 820 for a regular students and 120 for elementary school teacher training programs. These printed course materials can be utilized by other programs that has about similar curriculum or a taylor made program. Besides for utilizing the course materials the continuing program should be so designed that courses in this program can be transfer to a degree program.A certificate continuing education programs should be appropriate designed to meet not only the competency required for that program but also that the courses taken by students could be tranfers for a degree program. From the operational point of view of UT system the continuing education program could be attached in UT system without many difficulties as long as the courses of the program will be regarded as a different course although it uses the same course material.